Low-loss on-chip superconducting microwave circulator assisted by shunting capacitors - N. Pradeep Kumar; Dat Thanh Le; Prasanna Pakkiam; Thomas M. Stace; Arkady Fedorov (Physical Review Research)
Ferrite-free circulators that are passive and readily integratable on a chip are highly sought-after in quantum technologies based on superconducting circuits. In our previous work, we implemented such a circulator using a three-Josephson-junction loop that exhibited unambiguous nonreciprocity and signal circulation, but required junction energies to be within 1% of design values. This tolerance is tighter than standard junction fabrication methods provide, so we propose and demonstrate a design improvement that relaxes the required junction fabrication precision, allowing for higher device performance and fabrication yield. Specifically, we introduce large direct capacitive couplings between the waveguides, which based on the modeling we describe here, requires less stringent junction fabrication tolerance. We implement the design, and measure enhanced “circulation fidelity” above 97%, with optimized on-resonance insertion loss of 0.2 dB, isolation of 18 dB, and power reflectance of −15dB, in good agreement with model calculations.